Social status, preferences for redistribution and optimal taxation: A survey - Andrea Gallice (Kiel Institute for the World Economy (IfW), 2018)
The author reviews recent studies of how social status concerns influence individual preferences for redistribution and impact the design of optimal tax policies. He focuses on two aspects: the relevant dimension over which relative concerns are defined and the different formalizations of the notion of social status that the authors provide.
Keywords: D31; D62; H21; H23; 330; social status; redistribution; externalities; optimal taxation